Rolled copper foil, method for manufacturing copper-clad laminate, method for manufacturing flexible printed wiring board, and method for manufacturing electronic component
By controlling the S orientation distribution density and Ag concentration in the calendered copper foil, an excellent recrystallized texture is formed, which solves the problem of insufficient bending of the existing calendered copper foil, and achieves higher bending and longer bending fatigue life. , meets the strict needs of smartphones and other devices.
Patent Information
- Application Number
- CN202380042746.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-04
- Filing Date
- 2023-06-01
- Publication Date
- 2025-01-10
Smart Images

Figure BDA0005151528950000151 
Figure BDA0005151528950000161 
Figure BDA0005151528950000171
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a rolled copper foil, a copper-clad laminate, a method for producing a flexible printed circuit board, and a method for producing an electronic component. Background Art
[0002] Flexible printed circuits (FPCs) are made by bonding a metal conductive layer to a flexible insulating substrate such as a resin film. Usually, copper foil is used as the conductive layer, and in applications where flexibility is particularly required, rolled copper foil with excellent flexibility is used.
[0003] The usual FPC manufacturing steps are as follows. First, copper foil is bonded to a resin film. Regarding bonding, there is a method of coating a varnish containing a precursor of a polyimide resin on the copper foil and applying a heat treatment to imidize (casting method), and a method of overlapping and laminating a resin film having adhesive force with the copper foil (lamination method). The copper foil with a resin film bonded by these steps is called a copper clad laminate (CCL). After that, a circuit is formed by etching to complete the FPC.
[0004] As mentioned above, the rolled copper foil for FPC needs to be bendable. In order to provide a rolled copper foil for FPC that is easy to anneal at the curing temperature of the resin adhesive and has excellent bending resistance (bending fatigue life) after annealing, it is proposed to make the final cold rolling processing degree 90% or more.
[0005] Prior art literature:
[0006] Patent Literature
[0007] Patent document 1: Japanese Patent Application Laid-Open No. 4-228553. Summary of the invention
[0008] Technical problem to be solved by the invention
[0009] However, as electronic devices such as smartphones have become thinner, shorter, and more powerful in recent years, the bendability required of rolled copper foil has become increasingly stringent. As a result, copper foil manufactured using existing technologies is no longer able to meet customer needs.
[0010] Therefore, in one embodiment of the present invention, an object is to provide a rolled copper foil having higher bendability than before when converted into an FPC.
[0011] Solutions to technical problems
[0012] The present inventors have conducted various studies and found that a rolled copper foil having high bendability can be obtained by setting the orientation distribution density of the S orientation of the rolled copper foil to a predetermined value or more, and have created the invention as exemplified below. [1]
[0014] A rolled copper foil containing 99.9 mass % or more of Cu, the remainder of which is composed of inevitable impurities, and having an orientation distribution density of S orientation {123}<634> on the surface of the foil being 21.50 or more. [2]
[0016] The rolled copper foil according to [1], further comprising 100 to 360 mass ppm of Ag. [3]
[0018] The rolled copper foil according to [1] or [2], wherein the thickness is 4 to 35 μm. [4]
[0020] The rolled copper foil according to any one of [1] to [3], wherein the thickness is 6 to 35 μm. [5]
[0022] A method for producing a copper-clad laminate, comprising the step of bonding the rolled copper foil according to any one of [1] to [4] to a substrate. [6]
[0024] A method for manufacturing a flexible printed wiring board, comprising: using the copper-clad laminate manufactured by the method for manufacturing a copper-clad laminate according to [5] as a material to form a circuit. [7]
[0026] A method for manufacturing an electronic component includes: a step of manufacturing an electronic component having a flexible printed wiring board manufactured by the method for manufacturing a flexible printed wiring board according to [6].
[0027] Effects of the Invention
[0028] According to one embodiment of the present invention, it is possible to provide a rolled copper foil having higher bendability than ever before when converted into an FPC. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a schematic diagram showing the measurement method of the IPC sliding bending test in Examples 6 and 7 and Comparative Example 4.
[0030] Figure 2 This is a graph plotted based on Examples 6 to 7 and Comparative Example 4, with the horizontal axis representing the S orientation distribution density and the vertical axis representing the IPC sliding bending frequency. DETAILED DESCRIPTION
[0031] The present invention is not limited to the embodiments described below, and the components can be modified and embodied within the scope of the gist thereof. In addition, various inventions can be formed by appropriately combining a plurality of components disclosed in the embodiments.
[0032] It should be noted that the S orientation in this specification refers to the orientation of grains in which the {123} plane is parallel to the rolling plane and the <634> crystal direction is parallel to the rolling direction (RD), and is represented by the index {123}<634>. In addition, the "rolling direction" refers to the direction parallel to the direction in which the rolled object passes between the pair of work rolls.
[0033] [1. Rolled copper foil]
[0034] (Component)
[0035] In one embodiment, the rolled copper foil of the present invention contains 99.9 mass % or more of Cu, with the remainder being composed of inevitable impurities. In another embodiment, the rolled copper foil may be composed of pure Cu.
[0036] In another embodiment, the rolled copper foil may contain 100 to 360 ppm by mass of Ag as an alloy element from the viewpoint of more reliably obtaining higher bendability than before when FPC is formed and controlling the appropriate recrystallization temperature. In particular, it is preferred that the above-mentioned additive element be contained in tough pitch copper (TPC) of JIS H 3100 (C1100) or oxygen-free copper (OFC) of JIS H 3100 (C1020).
[0037] When the Ag concentration is greater than 360 mass ppm, under the influence of the increased recrystallization temperature of the rolled copper foil, even if the heat treatment in the casting method or lamination method is implemented, the recrystallization is sometimes insufficient. If it is assumed that there are unrecrystallized grains remaining in the rolled copper foil, the bendability of the FPC will be significantly reduced. In addition, if the Ag concentration is above 100 mass ppm, the amount of rolling strain introduced will increase, so the cubic texture after the CCL heat treatment is easy to grow, and the bendability is easy to increase.
[0038] It should be noted that the upper limit of the oxygen content in the rolled copper foil is, for example, 500 mass ppm or less. In addition, the lower limit of the oxygen content in the rolled copper foil is, for example, 0 mass ppm or more. Based on the viewpoint of reducing the amount of copper oxide (CuO) in the material, the oxygen content is preferably 50 mass ppm or less, and it is generally believed that copper oxide (CuO) will have an adverse effect on the bendability of the FPC.
[0039] The components of the rolled copper foil of the present invention can be measured by fluorescent X-ray analysis as a dry analysis. Specifically, the fluorescent X-ray analysis is measured using Simultix14 manufactured by Rigaku Corporation. For the analysis surface, a surface that has been cut or mechanically polished in a manner such that the surface maximum height roughness Rz (JIS B0601: 2013) is 6.3 μm or less can be used. In the case of sampling and analyzing a sample from the molten metal in the melt casting process in the manufacturing process of the rolled copper foil, it is cast into a shape of 30 to 40 mmΦ and a thickness of about 50 to 80 mm, and then cut into a thickness of about 10 to 20 mm, and then the cut surface is used as the analysis surface. The analysis surface is repeatedly cut or mechanically polished until the surface maximum height roughness Rz (JIS B0601: 2013) is 6.3 μm or less.
[0040] It should be noted that the composition of rolled copper foil can be determined by ICP emission spectrometry as a wet analysis in addition to the measurement using fluorescent X-ray analysis. Specifically, it can be measured using an ICP emission spectrometry device (ICP-OES) SPS3100 manufactured by Hitachi High-Tech Sciences, Ltd. In the case of ICP emission spectrometry, the sample is dissolved in a nitric acid aqueous solution (nitric acid: water = 1:1 by volume ratio) and diluted for use.
[0041] (Texture)
[0042] In one embodiment of the rolled copper foil of the present invention, the orientation distribution density of the S orientation {123}<634> on the surface (rolled surface) (hereinafter, also referred to as "S orientation distribution density") is 21.50 or more. If the S-oriented grains are well developed in the rolled texture of the rolled copper foil, a recrystallized texture with excellent bendability will be formed during the recrystallization caused by the heat treatment of the rolled copper foil, for example, bendability that is not dependent on the heating conditions during the manufacture of the copper-clad laminate can be obtained. The S orientation distribution density is preferably 22.0 or more in the lower limit, more preferably 22.2 or more, more preferably 22.3 or more, more preferably 22.5 or more, more preferably 22.8 or more, more preferably 23.0 or more, more preferably 23.5 or more, more preferably 23.9 or more, more preferably 24.0 or more, more preferably 24.5 or more, more preferably 24.9 or more, more preferably 25.0 or more, more preferably 25.5 or more, and more preferably 26.0 or more, based on the viewpoint of further improving the bendability. It should be noted that the upper limit of the S orientation distribution density is typically 30.0 or less, more typically 29.0 or less, considering the manufacturing cost.
[0043] Here, texture refers to the statistically biased orientation of the crystal orientation formed by processing and heat treatment, which depends largely on processing conditions and heat treatment conditions. Therefore, the inventors have found that in order to improve the S orientation distribution density, the control of the average crystal grain size after the final annealing and the processing degree of the final cold rolling are very important. The conditions of the average crystal grain size after the final annealing and the processing degree of the final cold rolling will be described below so they will not be repeated.
[0044] (Method for measuring S orientation distribution density)
[0045] First, the rolled copper foil is cut into a suitable size and used as a sample for measurement. The S orientation distribution density can be calculated by measuring the positive pole of the sample surface using an X-ray diffraction method. As an X-ray diffraction device, a SmartLab manufactured by Rigaku Corporation or an equivalent device is used to measure by Schulz reflection method. The measurement conditions are as follows.
[0046] <Measurement conditions>
[0047] X-ray tube: Cobalt (3kW packaged tube)
[0048] X-ray wavelength: Kα
[0049] Tube voltage: 40kV
[0050] Tube current: 25mA
[0051] Incident light slit: 2.5°
[0052] Divergence slit: 1 / 2°
[0053] Longitudinal limit slit: 2mm
[0054] Light receiving slit: 10mm
[0055] Light receiving parallel slit: 2.5°
[0056] Scattering slit: 9.975mm
[0057] Attenuator: Automatic
[0058] α angle step: 5°
[0059] β angle step: 5°
[0060] Counting time: 0.5 seconds / step
[0061] Vacuum degree: 1.00E-5Pa
[0062] Distance table settings (1) to (8)
[0063] (1) Distance between X-ray source and mirror: 90 mm
[0064] (2) X-ray source - Select the interval distance of the slit: 114mm
[0065] (3) X-ray source-IS (incident slit) distance: 173.5 mm
[0066] (4) Distance between X-ray source and sample: 300 mm
[0067] (5) Sample - RS (light receiving slit) 1 interval distance: 187 mm
[0068] (6) Sample - RS (light receiving slit) 2 interval distance: 300 mm
[0069] (7) Distance between RS (light receiving slit) 1 and RS (light receiving slit) 2: 113 mm
[0070] (8) Sample-detector interval distance: 331 mm
[0071] Option for package measurement: Schulz reflection method
[0072] software
[0073] Control software: XRD Measurement plug-in
[0074] Basic data processing: Data Manager plugin
[0075] Analysis: Texture plugin
[0076] <Pole determination>
[0077] Sample Information
[0078] Thickness: 0.012mm
[0079] Width: 20mm
[0080] Crystal system: cubic
[0081] Line absorption coefficient: 727.872 (1 / cm)
[0082] Pole determination conditions
[0083] Determination of hkl: 111, 200, 220
[0084] Measurement angle 2θ: 50.8°, 59.4°, 89.0°
[0085] - Stride length: 5°
[0086] Speed: 600° / min
[0087] Reflection method: Schultz
[0088] Background measurement: 1 point measurement
[0089] Measurement angle 2θ: 47.8°, 56.4°, 86.0°
[0090] (Measured at the side 3° lower than the test sample at each measurement angle, other conditions are the same as the test sample)
[0091] <Polar Figure Correction (Using SmartLab Studio II Texture)>
[0092] Enter a check mark in the check box of the following item and enter various data.
[0093] Background correction: Select from external data and input the background measurement results under each hkl mentioned above.
[0094] Absorption: Sample thickness, linear absorption coefficient, use the value of sample information.
[0095] Defocus Correction: Input the measurement results of a pre-measured fine copper powder.
[0096] Fine copper powder, with a purity greater than 99.5%, a particle size of 75 μm to 150 μm, and grade 1 copper (powder, 2N5) from Kanto Chemical Co., Ltd. (Cat. No. 07439-08)
[0097] Smoothing: Smoothing factor 1.0
[0098] standardization
[0099] However, in the Schulze reflection method, measurement becomes difficult when the incident angle of the X-ray with respect to the sample surface becomes low, so the angle range that can actually be measured is 0°≤α≤75° and 0°≤β≤360° on the positive pole diagram.
[0100] (It should be noted that α is an axis perpendicular to the rotation axis of the diffraction goniometer specified in the Schulz reflection method, and β is an axis parallel to the rotation axis.)
[0101] The obtained measurement results were converted into pole figures using the software Pole Figure Data Processing manufactured by Rigaku Corporation, and the ODF (Orientation Distribution Function) was calculated using the cube crystal orientation distribution function analysis program (product name: Standard ODF) manufactured by Nom Engineering Co., Ltd., and the pole density of the crystal orientation at all Euler angles was output.
[0102] <ODF analysis conditions>
[0103] Polar graph data
[0104] Crystal plane index: (100), (110), (111)
[0105] Weight: Each crystal face index is 1
[0106] α max =75
[0107] Δα=5
[0108] Δβ=5
[0109] Types of β angle: β = 0°, 5°, 10°, ..., 350°, 355°
[0110] Texture transformation: No
[0111] Crystallographic orientation distribution function
[0112] Number of expansions: 22
[0113] Threshold for zero density regions: 0.3
[0114] Display Section: Phi2 Section
[0115] Then, the Bunge method is read from these polar diagrams in Euler angles as The extreme density of S orientation distribution density is calculated.
[0116] (Average grain size after final annealing)
[0117] In one embodiment of the rolled copper foil of the present invention, the average grain size before the final cold rolling and after the recrystallization annealing 3 (final annealing) in the manufacturing example described below is preferably greater than 15 μm and less than 35 μm. By making the average grain size after the final annealing greater than 15 μm and less than 35 μm, it can be inferred that the crystal rotation is promoted during the final cold rolling, and the existence ratio of the S-oriented grains as the final stable orientation will increase. In addition, since the existence ratio of the S-oriented grains as the final stable orientation increases, during the recrystallization caused by the heat treatment of the rolled copper foil, the recrystallization texture with excellent bendability becomes developed and the bendability is improved.
[0118] (Method for measuring average crystal grain size)
[0119] Next, an example of a method for measuring the average crystal grain size is described. The average crystal grain size is measured by EBSD on the sample surface after final annealing. Here, EBSD (Electron Back Scatter Diffraction) refers to a technique for analyzing the crystal orientation using the reflected electron Kikuchi line diffraction (Kikuchi pattern) generated when an electron beam is irradiated on a sample in a SEM (Scanning Electron Microscope).
[0120] First, after removing a thickness of about 1 μm from the sample surface by electropolishing, the observation range of 1000 μm×1000 μm, which was set arbitrarily, was scanned with a step size of 3 μm. After that, the average grain size when the boundary with a crystal orientation difference greater than 5° was regarded as a crystal grain boundary was measured by the Area Fraction method. The above analysis was performed using OIM Analysis V8 manufactured by TSL Solutions Co., Ltd.
[0121] <Preparation of electrolyte solution (an example)>
[0122] 250ml distilled water
[0123] Phosphoric acid 125ml
[0124] ·Urea 2.5g
[0125] ·Ethanol Grade 1 125ml
[0126] 1-Propanol 25ml
[0127] <Electrolytic polishing conditions>
[0128] Applied voltage: 10V
[0129] Electrolysis time: 10 seconds
[0130] <EBSD measurement conditions, etc.>
[0131] ·SEM conditions
[0132] Equipment: Scanning electron microscope manufactured by JEOL Ltd. (JSM-IT500HR)
[0133] Type of electron gun: Electrolytic emission electron gun (Schottky type)
[0134] Electron gun emitter: ZrO tungsten cathode
[0135] Type of objective lens: External lens type
[0136] Focus correction: Yes (dynamic focus: 50)
[0137] Electron beam conditions
[0138] Accelerating voltage: 15 kV
[0139] Working distance: 15mm
[0140] Irradiation current: 15nA
[0141] SEM probe diameter: 0.5~2nm
[0142] Observation magnification: 90 times
[0143] ·EBSD device conditions
[0144] Detector: Slow-scan CCD camera manufactured by TSL Solutions Co., Ltd.
[0145] Data processing conditions
[0146] Data collection software: OIM Data Collection manufactured by TSL Solutions Co., Ltd.
[0147] Phase: Copper
[0148] CCD camera pixel count: 1394 × 1040 pixels
[0149] Binning (pixel combination): 8×8
[0150] Exposure: 8 milliseconds
[0151] Gain: 0.9~0.95
[0152] Background processing: Yes
[0153] Scanning method of measuring points: Hexagonal grid
[0154] Hough transform
[0155] (1) Hough Type: Classic
[0156] (2) Hough Resolution: Low
[0157] (3) Classic Hough
[0158] Convolution Mask: 9×9
[0159] Min Peak Magnitude: 5
[0160] Min Peak Distance: 23
[0161] Peak Symmetry: 0.75
[0162] Vertical Bias: 0
[0163] (4) General Parameter
[0164] Binned Pattern Size: 120
[0165] Theta Step Size: 1°
[0166] Rho Fraction: 90%
[0167] Max Peak Count: 8
[0168] Min Peak Count: 3
[0169] <Detailed settings of OIM Analysis V8 when calculating the average grain size>
[0170] ·Detailed settings of the Partition Properties window Grain Size tab
[0171] Input value for Grain Tolerance Angle: 5
[0172] Minimum Size [points]
[0173] Grains input value: 2
[0174] Anti-grains input value: 2
[0175] Input value for Minimum Confidence Index (minimum CI value): 0
[0176] Check the box for Apply partition before calculation: Check it.
[0177] Include grains at edges of scan in statistics checkbox: Check.
[0178] Twin Boundaries window (click Partition Properties
[0179] (Screen displayed when selecting Define in Partition Properties)
[0180] Check the box for Enforce matching between twin planes(K1)in grain A and grain B: Check.
[0181] Allowed tolerance between twin planes (K1s) [degrees]: 1
[0182] (Twins that are excluded are not specifically specified. Crystal grain boundaries include twins.)
[0183] Detailed settings of the New Chart window for calculating the average grain size
[0184] Type: Grain Size (diameter)
[0185] The value of Area within Average (average value according to the Area Fraction method) in the measurement result of Grain Size performed under the above-mentioned setting conditions is used as the average crystal grain size.
[0186] (thickness)
[0187] In one embodiment, the thickness of the rolled copper foil is, for example, 4 to 35 μm, and for example, 6 to 35 μm. The upper limit of the thickness of the rolled copper foil is, for example, 35 μm or less, and for example, 18 μm or less. In addition, the lower limit is, for example, 4 μm or more, and for example, 6 μm or more, and for example, 9 μm or more, and for example, 12 μm or more.
[0188] It should be noted that the thickness of the rolled copper foil can be measured by, for example, setting an X-ray generator on one surface side of the rolled copper foil and setting an X-ray detector on the other surface side, calculating the attenuation caused by the rolled copper foil based on the measured amount of penetrating X-rays, and converting it into the thickness of the rolled copper foil. For example, the weight of a 20 cm square rolled copper foil is measured, and the weight (g) / (density of the rolled copper foil (g / cm 3 )×Area of rolled copper foil (cm 2 )) Calculate the thickness of the rolled copper foil (It should be noted that the density of the rolled copper foil, as an example, the density of JIS H 3100 (C1020) oxygen-free copper is 8.94 g / cm 3 For another example, a digital length measuring machine (for example, Micro Digital MH-15M manufactured by Nikon) is used to measure at two or more arbitrary points, and the thickness of the rolled copper foil is calculated from the arithmetic mean of the thicknesses.
[0189] (Manufacturing Example of Rolled Copper Foil)
[0190] As an example of a method for manufacturing rolled copper foil, first, a melting furnace is used to melt raw materials such as copper to obtain a molten metal of the required components. Then, an ingot is manufactured by flowing the molten metal into a mold (casting). In order to prevent oxidation loss of copper, melting and casting are preferably carried out in a vacuum or in an inert gas atmosphere. Afterwards, the following steps are implemented in sequence: homogenization annealing, hot rolling, cold rolling 1, recrystallization annealing 1, surface cutting, cold rolling 2, recrystallization annealing 2, pickling / grinding, cold rolling 3, recrystallization annealing 3 (final annealing), and final cold rolling to form a rolled copper foil having the required thickness and the required properties. That is, in the present invention, the rolled copper foil can be said to basically refer to the copper foil after the final cold rolling.
[0191] It should be noted that according to the empirical speculation of the present inventors, the S orientation density distribution of the rolled copper foil after the final cold rolling is greatly affected by the average grain size after the final annealing and the processing degree of the final cold rolling when the rolled copper foil is manufactured according to the steps described below.
[0192] (Final Annealing)
[0193] In order to make the S orientation distribution density of the rolled copper foil after the final cold rolling easily developed, the conditions of the final annealing are appropriately set. Specifically, the conditions of the final annealing can be appropriately set so that the average grain size after the final annealing is greater than 15 μm and less than 35 μm. The conditions can be changed according to the composition of the copper material. Based on the annealing conditions disclosed in this embodiment and the comparative example, those skilled in the art can experimentally seek annealing conditions without too much trial and error.
[0194] (Final cold rolling)
[0195] By performing final cold rolling under the condition of a processing degree greater than 98% and less than 99%, a rolled copper foil can be obtained. The thickness of the rolled copper foil at this time is, for example, 4 to 35 μm, and also, for example, about 6 to 35 μm. It should be noted that the processing degree is defined as processing degree (%) = {(thickness before final cold rolling (mm) - thickness after final cold rolling (mm)) / thickness before final cold rolling (mm)} × 100.
[0196] [2. Method for manufacturing copper-clad laminate]
[0197] In one embodiment, the method for manufacturing a copper-clad laminate of the present invention comprises the step of bonding the rolled copper foil as described above to a substrate. As the substrate, for example, a resin film can be cited. In order to bond the resin film to the rolled copper foil, several techniques can be used.
[0198] For example, the following method can be used: using an adhesive formed of a thermosetting resin such as an epoxy resin, the rolled copper foil and the polyimide resin film are bonded together and heat-treated. Alternatively, the following method can be used: applying a varnish containing polyamic acid, which is a precursor of the polyimide resin, on at least one surface of the rolled copper foil and heat-curing it to form a polyimide coating on at least one surface of the rolled copper foil.
[0199] In addition, in the case of double-sided laminated rolled copper foil, there is a method of forming a single-sided copper-clad laminate and then pressing the rolled copper foil layer by heat pressing, and a method of sandwiching a polyimide resin film between two rolled copper foil layers and pressing them by heat pressing. These heat treatments are usually carried out under the conditions of 125 to 360°C and 30 to 400 minutes.
[0200] Furthermore, there is also a method of laminating the rolled copper foil and the resin film by using an adhesive without the heat treatment step. As the material of the resin film, polyester, polyimide, polyethylene terephthalate, polyethylene naphthalate, etc. can be listed, but it is not limited to these.
[0201] In addition, before laminating the rolled copper foil and the resin film, the rolled copper foil may be subjected to a roughening treatment, thereby increasing the bonding strength between the resin film and the rolled copper foil. For example, the roughening treatment may be performed under the following conditions.
[0202] <Roughening treatment conditions>
[0203] Liquid components: Cu10~20g / L, Co1~10g / L, Ni1~15g / L
[0204] pH: 1-4
[0205] Temperature: 30~50℃
[0206] Current density (Dk): 20~50A / dm 2
[0207] Time: 1 to 5 seconds
[0208] [3. Method for manufacturing flexible printed wiring board]
[0209] In one embodiment of the method for manufacturing a flexible printed circuit board of the present invention, the step of using a copper-clad laminate manufactured by the method for manufacturing a copper-clad laminate as described above as a material and forming a circuit is included. At this time, the copper-clad laminate can be used as a material and a circuit can be formed according to a known step to manufacture a flexible printed circuit board (FPC). For example, the following method can be cited: the resist is applied only to the necessary part as the conductor pattern on the rolled copper foil surface of the copper-clad laminate, and then the etching solution is sprayed on the rolled copper foil surface to remove the unnecessary rolled copper foil to form a conductor pattern, and then the resist is peeled off or removed to expose the conductor pattern. After the conductor pattern is formed, a protective covering film is usually attached.
[0210] (use)
[0211] Such FPC is an FPC used in a movable part in a hard disk, a hinge part and a sliding part of a mobile phone, the inside of a mobile phone, a head of a printer, an optical pickup part, a movable part of a notebook PC, etc. in an electronic component of an electronic device or an electrical device. It should be noted that the method for manufacturing an electronic component may include a step of manufacturing an electronic component having a flexible printed circuit board manufactured by the method for manufacturing a flexible printed circuit board.
[0212] [Example]
[0213] The present invention will be specifically described based on Examples and Comparative Examples. The following Examples and Comparative Examples are only specific examples given to facilitate understanding of the technical content of the present invention, and the technical scope of the present invention is not limited to these specific examples.
[0214] It should be noted that "OFC" in Table 1 and Table 2 refers to oxygen-free copper in accordance with JIS H 3100 (C1020) and "TPC" refers to tough pitch copper in accordance with JIS H 3100 (C1100).
[0215] [Examples 1 to 5, Comparative Examples 1 to 3]
[0216] [Manufacture of rolled copper foil]
[0217] First, in Examples 1 to 5 and Comparative Examples 1 to 3, an ingot is melted and cast, and the ingot has an alloy composition shown in Table 1 obtained by adding a specified metal to oxygen-free copper. It should be noted that the Ag content of the ingot is measured by the ICP emission spectrometry method described above. The ingot is processed in the following order to produce a rolled copper foil. It should be noted that the degree of processing in Table 1 is the thickness reduction rate in the final cold rolling, which is calculated by the following formula: degree of processing (%) = {(thickness before final cold rolling (mm) - thickness after final cold rolling (final product) (mm)) / thickness before final cold rolling (mm)} × 100.
[0218] <Steps (1) to (11)>
[0219] (Step 1) Homogenization annealing: The above ingot was heated at 920° C. and maintained for 2.5 hours.
[0220] (Step 2) Hot rolling: The ingot heated at 920° C. was rolled at room temperature to a thickness of 16 mm, and then rapidly cooled to room temperature by water cooling to obtain a strip-shaped metal material.
[0221] (Step 3) Cold rolling 1: rolling to a thickness of 10.5 mm.
[0222] (Step 4) Recrystallization annealing 1: The strip-shaped metal material is heated at 400° C. and maintained for 7.5 hours.
[0223] (Step 5) Surface cutting: The oxide scale layer on the surface is removed by surface cutting.
[0224] (Step 6) Cold rolling 2: rolling to a thickness of 1.5 mm.
[0225] (Step 7) Recrystallization annealing 2: Maintain in a furnace heated to 750°C for 30 to 120 seconds.
[0226] (Step 8) Pickling / Polishing: After immersion in a mixed acid of sulfuric acid and hydrogen peroxide, the oxide film on the surface of the material is removed by polishing.
[0227] (Step 9) Cold rolling 3: rolling to a thickness of 0.8 mm.
[0228] (Step 10) Recrystallization annealing 3 (final annealing): The annealing temperature and holding time are adjusted to obtain a specified grain size, and the strip metal material after cold rolling 3 is heated and kept warm respectively. Table 1 records the annealing conditions of each sample. It should be noted that in order to prevent oxidation, the above-mentioned strip metal material is wrapped and sealed with a rolled copper foil (thickness: 33 μm) of fully annealed tough copper (JIS H 3100 (C1100)) and the sealed body obtained is placed in a dryer. After heating and keeping warm, the sealed body is taken out of the dryer and placed in an atmospheric atmosphere for cooling. After being placed and cooled, the strip metal material is taken out from the sealed body. Then, the average grain size after the final annealing is determined by the above-mentioned method.
[0229] (Step 11) Final cold rolling: Finishing to a thickness of 0.012 mm (12 μm) to obtain rolled copper foil. In the final cold rolling, the two end sides of the strip metal material in the rolling direction are not fixed (free end state), and the strip metal material is passed between a pair of working rolls and rolled in a manner that tension does not act in a direction parallel to the rolling direction.
[0230] In addition, in Examples 1 to 5 and Comparative Examples 1 to 3, recrystallization annealing 3 was performed at the annealing temperature and holding time described in Table 1.
[0231] [Characteristics evaluation]
[0232] Next, in Examples 1 to 5 and Comparative Examples 1 to 3, a portion of the rolled copper foil obtained in the above-mentioned production was taken as each measurement sample, and the S orientation distribution density on the surface of the rolled copper foil was measured by the method described above using SmartLab manufactured by Rigaku Corporation. The results are shown in Table 1.
[0233] [Table 1]
[0234]
[0235]
[0236] (Examination of Example 1)
[0237] Comparing Examples 1 to 5 with Comparative Examples 1 to 3, it was found that the S orientation distribution density can be controlled by appropriately setting the average grain size after the final annealing, based on the final cold rolling processing degree being greater than 98% and less than 99%. In addition, comparing Example 3 with Example 4, it can be observed that the smaller the average grain size after the final annealing, the higher the S orientation distribution density tends to be.
[0238] [Examples 6 to 7 and Comparative Example 4]
[0239] [Evaluation of rolled copper foil]
[0240] <IPC sliding bending test>
[0241] In Examples 6 to 7 and Comparative Example 4, in order to confirm the relationship between the S orientation distribution density and the bendability, rolled copper foils having the S orientation distribution density of the surface (rolled surface) as described in Table 2 were prepared. A portion of the rolled copper foil was taken as each measurement sample. On the surface of one side of the measurement sample, after roughening plating treatment was performed with reference to the above-mentioned roughening plating treatment conditions, Pixio (trademark) FRS grade (thickness 25 μm) manufactured by Kaneka Co., Ltd. as a polyimide resin film was laminated on the roughening plating treatment side of the rolled copper foil, and pressed by hot pressing treatment at 360°C for 30 minutes, thereby producing a single-sided copper-clad laminate consisting of two layers of rolled copper foil and polyimide resin film. Afterwards, a known photolithography technique was used to form a circuit in a manner such that the circuit width (Line) of the rolled copper foil and the spacing (Space) between adjacent circuits were Line / Space=300μm / 300μm, and an FPC was produced. Next, a test piece was cut out from the obtained FPC so that the width was 12.7 mm and the length was 130 mm and the longitudinal direction of the test piece was parallel to the rolling direction. Figure 1 The IPC (Association of Printed Circuit Industries) bending test device 100 shown in the figure is used to measure the number of IPC sliding bendings on the test piece. The IPC bending test device 100 is a structure in which a vibration transmission component 20 is combined with a vibration driving body 10, and the test piece 30 is fixed to the device at a total of four points, namely, the part of the screw 40 indicated by the arrow and the top end of the vibration transmission component 20. When the vibration transmission component 20 is driven up and down, the middle part of the test piece 30 is bent into an arc with a specified curvature radius r. The IPC sliding bending test is carried out under the conditions of a curvature radius r of 2.5 mm (outer radius), a vibration stroke of 20 mm, and a vibration speed of 1500 times / minute.
[0242] It should be noted that in the IPC sliding bending test, the number of times until the fracture when bending is repeated under the above conditions is counted, and the number of test implementations under each condition is set to 4 times, and the IPC sliding bending test is implemented. The average value of the number of times until the fracture is obtained is used as the IPC sliding bending number and is shown in Table 2. It should be noted that the fracture mentioned here means that the electrical impedance of the FPC before the IPC sliding bending test has increased by 20%. The electrical impedance is measured by a 4-terminal method.
[0243] [Table 2]
[0244]
[0245] (Examination of Example 2)
[0246] Comparison of the results obtained in Examples 6 and 7 with the results obtained in Comparative Example 4 confirmed that by using a rolled copper foil having an orientation distribution density of S orientation {123}<634> of 24.9 or more, the rolled copper foil obtained in Examples 6 and 7 had better bendability than ever before when used to make an FPC.
[0247] It should be noted that the results are plotted with the horizontal axis being the S orientation distribution density of each sample and the vertical axis being the number of IPC sliding bending times, as shown in Figure 2 In addition, the approximate straight line result is calculated by the straight line approximation function of the approximate curve of Microsoft (registered trademark) Excel and Figure 2 The approximate formula of the straight line is shown together with the square of R. The closer the square of R is to 1, the more appropriately the approximate straight line shows the tendency of the experimental data. It can be seen that there is a positive proportional correlation between the S orientation distribution density and the IPC sliding bending number.
[0248] When the IPC sliding bending times of 230,000 or more is selected as the qualified line for FPC, the IPC sliding bending times is increased by about 20% or more compared with the comparative example 4 as a conventional product. The S orientation distribution density of the IPC sliding bending times of 230,000 can be based on Figure 2 The approximate straight line of is calculated to be 21.499. Considering this, it is estimated that by using a rolled copper foil having an S orientation distribution density of 21.50 or more, a rolled copper foil having higher bendability than before can be provided when FPC is formed.
[0249] Explanation of symbols
[0250] 10: Vibration drive body
[0251] 20: Vibration transmission components
[0252] 30: Test piece
[0253] 40: Screw
[0254] 100:IPC bending test device
[0255] r: radius of curvature
Claims
1. A rolled copper foil comprising 99.9 mass % or more of Cu, the remainder of which is composed of inevitable impurities, and wherein the orientation distribution density of the S orientation {123}<634> on the surface is 21.50 or more. 2 . The rolled copper foil according to claim 1 , further comprising 100 to 360 mass ppm of Ag.
3. The rolled copper foil according to claim 1 or 2, which has a thickness of 4 to 35 μm. 4 . The rolled copper foil according to claim 1 , which has a thickness of 6 to 35 μm.
5. A method for manufacturing a copper-clad laminate, comprising: A step of bonding the rolled copper foil according to any one of claims 1 to 4 to a substrate.
6. A method for manufacturing a flexible printed circuit board, comprising: A step of using the copper-clad laminate produced by the method for producing a copper-clad laminate according to claim 5 as a material to form a circuit.
7. A method for manufacturing an electronic component, comprising: A step of manufacturing an electronic component including the flexible printed wiring board manufactured by the method for manufacturing a flexible printed wiring board according to claim 6.
Citation Information
Patent Citations
Bending resisting rolled copper foil
JP1992228553A